Health Belief Model Pada Penderita Demam Berdarah Dengue di Wilayah Kerja Puskesmas Mamajang Kota Makassar - Surahmawati Surahmawati; Andi Susilawaty; Muhammad Saleh; Muhammad Zul Bashar (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2019)
Dengue Haemorrhagic Fever (DHF) is an acute fever with two or more symptoms such as retro-orbital pain, headache, skin rashes, bleeding, and leukopenia that lasts between 2-7 days. The primary vector of DHF is Aedes aegypti mosquito. This research investigates the perceptions of patients with Dengue Haemorrhagic Fever (DHF) within the working area of Mamajang Health Centre in Makassar City. It uses qualitative method with a phenomenological approach in scrutinising the issue. The research data are obtained through in-depth interviews with several informants. The findings suggest some interesting information about the issue. first of all, most informants believe that their vulnerability toward Dengue Haemorrhagic Fever (DHF) is due to the environmental condition, symptoms, times of disease transmission, patients, and the consequences of catching the disease. They also view Dengue Haemorrhagic Fever (DHF) as an alarming disease because it lowers the patients' productivity, prohibits them from working for earning income, as well as causes casualties. This research further reveals informants' perception of the benefits of some Dengue Haemorrhagic Fever (DHF) prevention programs that they have participated in. In addition to reducing their risk of catching the disease, the prevention programs also allow them to enjoy a cleaner and tidier neighbourhood. However, they also claimed that they had also faced some challenges in implementing the programs. The pesticides contain various additive substances that they deem dangerous for their health and thus they have to be careful in using them. Besides, they find that using sleeping nets are unpleasant during warmer days. Although they have complaints, most informants believe that the sacrifices are worth for their health and wellbeing. They also actively prevent Dengue Haemorrhagic Fever (DHF) by burying unused stuff, covering water storages, regularly cleaning bathtubs, draining puddles, as well as using pesticides. Most informants are aware of the importance of Dengue Haemorrhagic Fever (DHF) prevention programs even without constant reminders from people around them.Keywords: Dengue Haemorrhagic Fever, Health Belief Model, Aedes Aegypti.